An analysis of the influence of shadow economy on economic development - Dima, Bogdan; Dima, Ştefana Maria; Preda, Ciprian (Serbian Journal of Management, 2026)
The shadow economy is an umbrella concept that covers different aspects of the informal economic sectors. Conventional wisdom states that an increased size of the shadow economy hampers economic growth. However, we adopt a more nuanced conceptual framework, considering the mixed effects exercised by the shadow economy on economic development and full employment of labour resources. Thus, we estimate the size of the shadow economy employing a Multiple Indicators and Multiple Causes model. To cope with the uncertainty that emerges from the large set of potential determinants of economic development, we employ the resulting proxy of the shadow economy in a Bayesian Model Averaging/Weighted-Average Least Squares. Alternative approaches to data are considered for a robustness check. We find that for a dataset of 124 post-industrial and developing economies covering the period between 1991 and 2017, the shadow economy can both positively and negatively affect economic development. Our results show that the ‘net’ effect exercised by the shadow economy on the official sectors is an open question. The main implication is that any policy aiming to reduce the size of the shadow economy should be accompanied by an improvement of the economy’s formal sectors to absorb unemployment.